Comparative analysis of Kurikulum 2013 and Kurikulum Merdeka implementation on character development in physical education - Akhmad Mar’i Muyassar (Inovasi Kurikulum, 2025)
The curriculum not only regulates learning content but also directs all core aspects of education, including learning, teaching, assessment, and the creation of an inclusive and relevant learning environment. This study aims to analyze and compare the implementation of Kurikulum 2013 and Kurikulum Merdeka in terms of student character development within physical education. The existing character crisis, marked by issues like a lack of discipline and honesty, underscores the importance of evaluating curriculum effectiveness in fostering positive values. This study employed a quantitative descriptive method, involving a sample of students from public and private schools in Bandung selected through cluster sampling. Data were collected using a structured questionnaire adapted from the Youth Sport Value Questionnaire and the Questionnaire of Attitudes in Sport to measure dimensions of values—including moral, competence, and status—and attitudes, which encompass commitment, habits, cheating, and gamesmanship. The results revealed that the majority of students under both curricula fell into the 'moderate' category for character development. Further statistical analysis showed no significant difference between the two curriculum groups. It is concluded that while both curricula have an influence, there is no significant difference in their impact on character development, as their effectiveness tends to be moderate and is heavily influenced by other factors, such as teacher competence and the school environment.   Abstrak Kurikulum tidak hanya mengatur konten pembelajaran, tetapi juga mengarahkan seluruh aspek inti pendidikan, seperti pembelajaran, pengajaran, penilaian, dan lingkungan belajar yang inklusif dan relevan. Penelitian ini bertujuan untuk menganalisis dan membandingkan implementasi Kurikulum 2013 dengan Kurikulum Merdeka terhadap pengembangan karakter murid dalam pembelajaran pendidikan jasmani. Berangkat dari adanya krisis karakter seperti kurangnya disiplin dan kejujuran, evaluasi efektivitas kurikulum dalam membentuk nilai-nilai positif menjadi sangat penting. Studi ini menggunakan metode deskriptif kuantitatif, melibatkan sejumlah murid dari sekolah negeri dan swasta di Kota Bandung yang dipilih melalui teknik cluster sampling. Data dikumpulkan menggunakan kuesioner terstruktur yang diadaptasi dari Youth Sport Value Questionnaire dan Questionnaire of Attitudes in Sport untuk mengukur dimensi nilai meliputi moral, kompetensi, dan status serta sikap, yang mencakup komitmen, kebiasaan, kecurangan, dan permainan. Hasil penelitian menunjukkan bahwa mayoritas murid pada kedua kurikulum berada dalam kategori pengembangan karakter "sedang". Analisis statistik lebih lanjut menunjukkan tidak terdapat perbedaan yang signifikan antara kedua kelompok kurikulum tersebut. Disimpulkan bahwa meskipun kedua kurikulum memberikan pengaruh, tidak ada perbedaan signifikan dalam dampaknya terhadap pengembangan karakter, di mana efektivitasnya cenderung moderat dan sangat dipengaruhi oleh faktor lain seperti kompetensi guru dan lingkungan sekolah. Kata Kunci: Kurikulum 2013; Kurikulum Merdeka; pengembangan karakter; pendidikan jasmani; studi komparatif